GAMBARAN PELAKSANAAN TUGAS KESEHATAN KELUARGA DALAM PEMELIHARAAN KESEHATAN LANJUT USIA DI DUSUN KARANGNONGKO DESA BALONGMOJO KECAMATAN PURI KABUPATEN MOJOKERTO - Nur Hidayati, Rina (JURNAL KEPERAWATAN BINA SEHAT, 2015)
The process of aging is a state that it can not be avoided. Aging, the elderly degenerates on the functioning of body systems.Elderly who decreases function of both physiological and psychological, let alone a chronic illness needs the support and assistance of the family in health care efforts.Family understanding about family health task is necessary, so that the family can be independent in elderly health maintenance efforts.The purpose of this research described the task of family health in the elderly health maintenance efforts Karangnongko Village Balongmojo Castle District of Mojokerto.This research used a descriptive design, cross sectional approach with 30 samples were taken by purposive sampling.Result was obtained most of the implementation of the tasks of family health at the second level of independence that was as much as 40%. In this case,the family was not able to conduct promotive and preventive health care in an effort elderly as well.This research showed that the implementation of family health task has not yet reached the optimum level of independence.Department of Health should promote concerted efforts by reoptimalisasi role in fostering community health nursing with home health care in family with elderly .The family coaching is more emphasis on promotive and preventive actively for the implementation of tasks in the family health,elderly health maintenance can be done independently.Keywords: Task of Family Health, Elderly